2019
DOI: 10.1002/jcu.22794
|View full text |Cite
|
Sign up to set email alerts
|

Shear‐wave elastography of the liver in a healthy pediatric population

Abstract: Purpose The aim of this study was to determine the elastic modulus values of normal liver tissue in school‐age children by shear wave elastography (SWE) and to study the factors that influence these stiffness measurements. Methods Six hundred and four school‐age children (295 girls and 309 boys) who were recruited at a hospital and had normal results of specific laboratory tests and imaging studies underwent SWE examinations. The elastic modulus values were obtained in segment V and VI for each subject and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The latter studies demonstrated age-related differences in SWE, which we could confirm only by bivariate correlation, but have to negate considering multiple covariates. The absolute SWE values in our cohort (mean 4.37 ± 0.60 kPa) are comparable to already published data in children (16, [44][45][46][47] but lower than the mean values in other studies (48)(49)(50), possibly due to the usage of different ultrasound devices. Fasting duration did not significantly influence SWE in our study, as suggested by Simkin et al (51).…”
Section: Shear Wave Elastographysupporting
confidence: 88%
“…The latter studies demonstrated age-related differences in SWE, which we could confirm only by bivariate correlation, but have to negate considering multiple covariates. The absolute SWE values in our cohort (mean 4.37 ± 0.60 kPa) are comparable to already published data in children (16, [44][45][46][47] but lower than the mean values in other studies (48)(49)(50), possibly due to the usage of different ultrasound devices. Fasting duration did not significantly influence SWE in our study, as suggested by Simkin et al (51).…”
Section: Shear Wave Elastographysupporting
confidence: 88%
“…Impairment of wholekidney elasticity probably requires the profound histological changes of diabetic nephropathy. Previous studies reported reduced global kidney SWV and eGFR values in both patients with and those without severe proteinuria 6,12,19 . However, such findings probably require kidney damage that is more severe than glomerulosclerosis, such as irreversible tubulointerstitial fibrosis and vascular changes.…”
Section: Discussionmentioning
confidence: 89%
“…Although the SWVs were correlated positively with the extent of liver fibrosis 19 , they were correlated negatively with the CKD stage and eGFR 6,12 . The mechanism underlying the inverse relationship between kidney stiffness and the eGFR in CKD patients remains unclear.…”
Section: Discussionmentioning
confidence: 94%
“…Several ultrasound-based techniques have been investigated in recent years for liver stiffness assessment (6,7). Point shear wave elastography (8)(9)(10)(11), transient elastography (10)(11)(12)(13), acoustic radiation force impulse (10,11,14,15), 2D shear wave elastography (10,11,16), and supersonic shear wave elastography (17) have been validated in the pediatric population to determine normal stiffness values, or to detect and stage liver fibrosis. The advantages of these methods are the low price, rapid assessment of liver stiffness, and the noninvasive character that allows for regular follow-up.…”
Section: Introductionmentioning
confidence: 99%